The EFFECT OF TAXES, BONUS MECHANISM, TUNNELING INCENTIVES ON THE INDICATIONS OF TRANSFER PRICING IN MINING COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE (2018-2021) - Devi Ayu Putri; Indah Cahya Sagala; Yani Rugun Simanullang (Jurnal Ekonomi, 2023)
This study aims to examine the effect of taxes, bonus mechanisms and tunneling incentives on transfer pricing of mining companies listed on the Indonesia Stock Exchange in 2018-2021 either partially or simultaneously. The independent variable in this study is tax (X1) bonus mechanism (X2) and tunneling incentive (X3) while the dependent variable in this study is transfer pricing. This type of research is quantitative research conducted using secondary data in the form of data from annual reports in 2018-2021. The population in this study are mining companies listed on the Indonesia Stock Exchange in 2018-2021. The sampling method used purposive sampling and obtained a sample of 20 companies or 80 samples of companies. Hypothesis testing was carried out using logistic regression analysis with the help of the SPSS v.25 program and Microsoft Office Excel software. The results of this study indicate that the variables of tax, bonus mechanism and tunneling incentive have a positive and significant effect on transfer pricing of mining companies. This study shows that simultaneously taxes, bonus mechanisms, tunneling incentives have a positive effect on transfer pricing.